(untitled) (Research, Society and Development, 2021)
Objective: to identify scientific evidence about factors related to the beginning of early sexual practices in adolescence. Method: Integrative review of articles published in Portuguese, English or Spanish, in the LILACS, BDENF, MedLine, CINAHL and Web of Science databases. The descriptors Adolescent, Sexuality, Sexual Behavior, Sexual Intercourse and Coitus were used, with thirty-eight articles selected for analysis. Results: in the selected studies, thirty-seven were quantitative and one qualitative. The results gave rise to three classes: Family and peer ties; Vulnerable situations and health-promoting actions. The classes showed that the factors related to the initiation of early sexual practices in adolescence are related to different scenarios, capable of influencing in a positive or negative way the adolescents’ decisions about the beginning of their sexual life. Conclusion: The study allowed a critical reflection on the factors that contribute to determine the initiation of early sexual practices in adolescence, as well as to learn protective strategies, which contribute to postpone the beginning of sexual practices.